2020
DOI: 10.1002/pen.25597
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and in‐vitro analysis of poly(ε‐caprolactone)‐“Jackfruit” Mucilage blends for tissue engineering applications

Abstract: Jackfruit mucilage (JM) obtained from the fruit, Artocarpus heterophyllus was melt blended with poly(ε‐caprolactone) (PCL). The physical properties of the blends with more than 60 wt% PCL were investigated. Depression in the equilibrium melting temperature (Tmo) and the presence of extinction rings in the spherulites of PCL in the blends confirmed miscibility of the two components. The carbonyl and the COC groups of PCL and JM were responsible for the interactions as identified by Fourier transform infrared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…The hydrolysis reaction is much faster as the soil dries while PDMS undergoes extensive degradation when exposed to dry soils. It is discovered that the soil's clay components encourage this rearrangement process 5–8 …”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…The hydrolysis reaction is much faster as the soil dries while PDMS undergoes extensive degradation when exposed to dry soils. It is discovered that the soil's clay components encourage this rearrangement process 5–8 …”
Section: Introductionmentioning
confidence: 99%
“…The inclusion of PDMS content can decrease the transition temperature of shape, that is, permanent shape to temporary shape or vice versa, whereas the change in PCL chain length and increase in the crosslink density influence the shape memory properties, that is, shape fixity and shape recovery 14 . PCL‐PDMS‐PCL triblock copolymers were studied experimentally under a simulated body fluid environment by several researchers 7–9,15 . Azemar et al reported that the hydration of PCL‐PDMS‐PCL copolymers increased with the addition of PDMS and PCL end‐chain degraded into small oligomers in a hydrolytic degradation study 8 .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations